Using log variables in a learning management system to evaluate learning activity using the lens of activity theory. Issue 4 (19th May 2017) - Park, Yeonjeong; Jo, Il-Hyun
Abstract : As the advance of learning technologies and analytics tools continues, learning management systems (LMSs) have been required to fulfil the growing expectations for smart learning. However, the reality regarding the level of technology integration in higher education differs considerably from such expectations or the speed of advances in educational technologies. This research aimed to evaluate the current activation levels and usage patterns of a LMS. A large data-set was analysed, which included the online activity information from 7940 courses. Through data pre-processing, general indicators reflecting login frequencies of the virtual campus and activity - based indicators presenting the activation patterns of diverse functions provided by Moodle were derived. Activity theory was applied to interpret the results of analysis, since it has been recognised as a powerful framework to understand phenomena encompassing interactive systems. Further, time-series investigation over three consecutive semesters allowed observation of historical changes. The results revealed considerably low use of the virtual campus with only slight changes, as well as significantly different activity patterns across course attributes and colleges. Contradictions among components in the activity system are discussed, along with the implications for improving teaching and learning with LMS in higher education.